2019
DOI: 10.1177/1090198118822724
|View full text |Cite
|
Sign up to set email alerts
|

Social Needs and Health-Related Outcomes Among Medicaid Beneficiaries

Abstract: Unmet social needs—including food, housing, and utilities—have been associated with negative health outcomes, but most prior research has examined the health associations with a single unmet need or analyzed samples that were homogeneous along one or more dimensions (e.g., older adults or patients with chronic health conditions). We examined the association between unmet social needs and psychosocial and health-related outcomes in a sample of Medicaid beneficiaries from 35 U.S. states. In 2016-2017, 1,214 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Medicaid itself serves as a proxy for other social determinants of health, as research has demonstrated that most medicaid beneficiaries lack in at least one social need-i.e., adequate income, food, housing, utilities, etc. [53]. These unmet needs have been associated with an increased number of chronic conditions as well as decreased physical functioning and higher mortality [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicaid itself serves as a proxy for other social determinants of health, as research has demonstrated that most medicaid beneficiaries lack in at least one social need-i.e., adequate income, food, housing, utilities, etc. [53]. These unmet needs have been associated with an increased number of chronic conditions as well as decreased physical functioning and higher mortality [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…[53]. These unmet needs have been associated with an increased number of chronic conditions as well as decreased physical functioning and higher mortality [53][54][55]. Recognizing this, the Centers for Medicare and Medicaid Services modernized its operations in 2016 to promote practices that look beyond clinical care and to address patients' social needs [56].…”
Section: Discussionmentioning
confidence: 99%
“…Directly comparing the overall results to other studies is challenging because of differences in the populations being screened 21,23,27-31 and, more importantly, differences in the screening tools, either based on the number or types of risks being screened for 23,30,[32][33][34] or the wording of the instrument. [35][36][37][38] Among more comparable studies, Berkowitz et al 20 screened 5,125 adult primary care patients in Boston, finding that 34.6% of the population had at least 1 risk.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, long-term maintenance of diabetes control is still an issue for some individuals even after DSME courses are completed. 12 Inequities found in the social determinants of health add to the struggles of diabetes management including low-income, 13 inadequate housing, 14 behavioral health needs, 15 and lack of health insurance. 16 In addition, lack of resources/support for medications and doctor visits, 17 transportation, 4 day labor jobs/choice between work and doctor visits, 18 culture and language capabilities 19 are other barriers to diabetes self-management found among Mexican American populations.…”
Section: Introductionmentioning
confidence: 99%